Implementasi Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Cahaya Anugrah Firdaus - Riky Nugraha; Syifa Pramudita Faddila (Madani: Jurnal Ilmiah Multidisiplin, 2023)
PT Cahaya Anugrah Firdaus was established in 2014. CAF was founded by Moch. Yanuar Anugrah who wanted to establish an IT company that does not only focus on technology. PT CAF Technology is located at Jl. Akuntansi No. 2 Cigadung, Cibeunying Kaler, Bandung City, West Java 40191. The company has several services for IT & Solution including IT service management, database application, web design, mobile apps, interactive multimedia, product communication, and server and networking. The purpose of this research is to find out the implementation of work discipline on employee performance at PT Cahaya Anugrah Firdaus, with an implementative method in the form of descriptive. The results of observations supported by company data show attendance in April and May through the Fingerprint Machine there are several employees in the company who still pay less attention to attendance, the problem factor is affected by traffic problems when departing to the company, the solution applied to these conditions is that one of them is the company must improve the fingerprint attendance machine.Â  From the problems observed, the authors can conclude that employee discipline at PT. Cahaya Anugrah Firdaus is still not paying attention to attendance so that it has an impact on employee performance.